Perceived Barriers and Self-efficacy: Impact on Self-care Behaviors in Adults with Type 2 Diabetes - E Shakibazadeh; A Rashidian; B Larijani; D Shojaeezadeh; MH Forouzanfar; A Karimi Shahanjarini (Tehran University of Medical Sciences, 2009)
Normal 0 false false false MicrosoftInternetExplorer4 st1":*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin:0pt; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} Background & Aim: Regarding the importance of determining the determinants of diabetes self-care, this study aimed to examine two major determinants of self-care activities, i.e. perceived barriers, and perceived self-efficacy among type two diabetic patients in Tehran, Iran. "n"n Methods & Materials: In this cross-sectional study, 128 patients were recruited to the study using convenience sampling. The validated diabetes instruments were completed by the patients. The included participants aged older than 18 years. Data were analyzed using bivariate correlation and path analysis. "n"n Results: The mean score of the perceived barriers and perceived self-efficacy were 3.05 and 2.18, respectively. The maximum score of self-care was 4.18. There was a positive correlation between self-efficacy and the self-care (r=0.22; P<0.01). Positive correlations were also found between education with self-efficacy and self-care (r=0.28; P<0.05), (r=0.29; P<0.05). There was a negative correlation between perceived barriers and self-care behaviors (r=-0.68; P<0.000). Using serial multiple regressions and path analysis, we had a final model (RMSEA=0.05; GFI=0.95; CFI=0.98; P=0.44; and Chi-Square=26.5). This model showed that perceived barriers were the strongest predictor for self-care behaviors. Perceived barriers mediated the effect of self-efficacy on the self-care behaviors. "n"n Conclusion: The intervention efforts that address the studied determinants related to self-care behavior could potentially impact type two diabetic patients' self-care activities. These determinants should be mentioned in the program developing."n"n  "n"n Key words: self efficacy, self-care, diabetes mellitus, determinants